(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Communism is the political, social and economic ideology. It the Brain-Child and eminent German born Scholar, KarlMarx. His well-known works “Communist Manifesto” and “Das Capital “contained his ideology. Between 1880-1917 England, Russia were greatly shocked with the popularity of communist ideology of Marx. His appeal for equality, share for workers and peasants in the profits of capitalist classes turned the Rulers and Capitalists against him. But all the attempts to curb his ideology proved futile. Finally his friendship with Hegel and their combine efforts put an end to Czar Rule in Russia in 1917. The Indians were also got attracted towards communism due to various reason after 1918. In spreading communist philosophy, Indian Revolutionaries, Muslim leaders, Russian communist leaders played key role. After the success of Bolshevik Revolution in Russia under Lenins leadership the entire world was terrified with the bloodshed of communists. The world wide counter reaction was greated. Class struggle was the pillar of communism.